2018
DOI: 10.1167/tvst.7.2.14
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Region-of-Interest Approach for Detecting Progressive Glaucomatous Macular Damage on Optical Coherence Tomography

Abstract: PurposeTo evaluate a manual region-of-interest (ROI) approach for detecting progressive macular ganglion cell complex (GCC) changes on optical coherence tomography (OCT) imaging.MethodsOne hundred forty-six eyes with a clinical diagnosis of glaucoma or suspected glaucoma with macular OCT scans obtained at least 1 year apart were evaluated. Changes in the GCC thickness were identified using a manual ROI approach (ROIM), whereby region(s) of observed or suspected glaucomatous damage were manually identified when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Importantly, the retest variability for ROI analysis was excellent at ±1.3 µm. (Wu et al 2018b). As in study manual ROI analysis was superior to automated ROI analysis for longitudinal detection of macular inner retinal layer atrophy.…”
Section: Brain 2019mentioning
confidence: 80%
“…Importantly, the retest variability for ROI analysis was excellent at ±1.3 µm. (Wu et al 2018b). As in study manual ROI analysis was superior to automated ROI analysis for longitudinal detection of macular inner retinal layer atrophy.…”
Section: Brain 2019mentioning
confidence: 80%
“…Further, progressive changes can be better detected by following a region of interest (ROI) than by using summary metrics from OCT printouts, such as average global cpRNFL thickness. 2,34,35…”
Section: When Do You Look At Oct Images?mentioning
confidence: 99%
“…In fact, we can still make use of the segmentation algorithms to define a ROI, but we should follow this region both quantitatively and qualitatively. 34 35 . This ROI can be a small abnormal region in cases of early glaucoma and small regions of preserved cpRNFL in the case of advanced glaucoma (Fig.…”
Section: A Comparison To An Interpretation Of Mri Scans Of the Brainmentioning
confidence: 99%
“…However, recent studies have revealed how neuroretinal parameters in the macula and posterior pole (outside of the peripapillary region) could also provide important information about disease progression 1014,22,23 that could be exploited to further improve the power to detect a significant treatment effect. Furthermore, analytical methods that limit the evaluation of progression within regions of established glaucomatous damage (to minimize the contribution of measurement variability from non-damaged regions) could further reduce sample size requirements 2326 .…”
Section: Discussionmentioning
confidence: 99%